Prenatal mobile applications reported in the scientific literature: a scoping review - Chaves, Arlane Silva Carvalho [UNESP]; Silva, Jhonata Gabriel Moura; de Souza de Jesus, Layane Mota [UNESP]; Spiri, Wilza Carla [UNESP]; Jensen, Rodrigo (FapUNIFESP (SciELO), 2024)
Objective: To map the prenatal mobile applications described and/or evaluated in the scientific literature. Method: Scoping review, based on JBI recommendations, with a time frame from 2017 to 2022. The searches were carried out in October/2023 in the following databases/portals: Lilacs via BVS, Web of Science, MEDLINE, Cochrane Database of Systematic Reviews, Scopus, CINAHL, and the Thesis and Dissertation Bank of the Coordination for the Improvement of Higher Education Personnel (CAPES). Results: Forty-nine studies were analyzed, including 45 articles, three dissertations and one thesis, published in Portuguese and English. The applications are intended for health education/self-care (46.9%), clinical monitoring (28.5%), for use by health professionals (16.3%), research/data collection (6.1%) and professional education (2%). Conclusion: The applications described and/or evaluated in the studies are diverse in their purposes and public and confirm the inclusion of mobile technology in the care and health monitoring of pregnant women.+
Aplicaciones móviles de prénatal reportadas en la literatura científica: una revisión de alcance
Aplicativos móveis de prénatal relatados na literatura científica: uma revisão de escopo
Keywords: Aplicaciones Móviles; Aplicativos Móveis; Atención Prenatal; Cuidado Pré-Natal; eHealth Strategies; Estrategias de eSalud; Estratégias de eSaúde; Informática Aplicada a la Enfermería; Informática em Enfermagem; Mobile Applications; Nursing Informatics; Prenatal Care; Review; Revisión; Revisão